From the camilos to the peronist comandos of liberation in the origins of montoneros - Salcedo, Javier (Revista de Historia Social y de las Mentalidades, 2019)
In September, 1966, there appeared the first issue of Cristianismo y Revolución (Christianity and Revolution), a magazine that was part of a radicalized expression of the Christian-Marxist Dialogue in Argentina. Several members of the encompassing political group (which would eventually become military in nature) identified themselves as Camilo Torres Comandos. Months later, they would change the name to Peronist Comandos of Liberation. This article seeks to examine existing bibliography as well as written and oral testimonies to elucidate if the Peronist identity of certain militant original members and their decision to turn to armed struggle took shape before or during the publication of the thirty issues of said magazine. Furthermore, this work aims to explore if Cristianismo y Revolución was a senseconstruction tool to “Peronize” its readers.